2011
DOI: 10.1007/s00232-011-9394-2
|View full text |Cite
|
Sign up to set email alerts
|

SMURF and NEDD4: Sharp Shooters Monitor the Gate Keepers and Ion Traffic Controllers of Lead Astray Cell

Abstract: It is becoming increasingly apparent that a complex bar code underlies the quantitative aspects of extracellular signal regulation. Cell type-specific and context-dependent transcriptional programs are triggered by sophisticated nanomachinery consisting of HECT enzymes which monitor signal generation, transduction and termination. How the HECT enzymes safeguard spatiotemporal organization was a fundamental question towards understanding the process of protein degradation and its functions in diverse biological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…1 and 4), which suggests that elevated WWP1 level may be one of the mechanisms for oncogenesis of prostate cancer. It has been shown that abrogation of smurfs potentiated TGF-mediated antineoplastic activity and simultaneously suppressed genomic instability by activating DNA repair proteins, suppressing FLIP (a protein that negatively regulates apoptosis) and elevating TRAIL (a positive regulator of apoptosis), which indicated a cancer-fostering role of smurfs (11). In the present study, we have demonstrated that both the mRNA and protein levels of Smurf1 and Smurf2 in prostate cancer tissues are obviously increased compared to those in benign prostate hyperplasia (Figs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 and 4), which suggests that elevated WWP1 level may be one of the mechanisms for oncogenesis of prostate cancer. It has been shown that abrogation of smurfs potentiated TGF-mediated antineoplastic activity and simultaneously suppressed genomic instability by activating DNA repair proteins, suppressing FLIP (a protein that negatively regulates apoptosis) and elevating TRAIL (a positive regulator of apoptosis), which indicated a cancer-fostering role of smurfs (11). In the present study, we have demonstrated that both the mRNA and protein levels of Smurf1 and Smurf2 in prostate cancer tissues are obviously increased compared to those in benign prostate hyperplasia (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…The neural precursor cell-expressed developmentally downregulated gene 4 (Nedd4) family of ubiquitin ligases (E3s) is characterized by a distinct modular domain architecture, with each member consisting of a C2 domain, 2-4 WW domains, and a hECT-type ligase domain (10). In Nedd4 family, smad ubiquitination regulatory factors (smurfs) are negative regulators of the transforming growth factor (TGF) signal-transduction cascade, which has antineoplastic activity in prostate cancer, indicating a cancer-fostering role of smurfs (11). The gene for WW domain containing E3 ubiquitin protein ligase 1 (WWP1), another member of Nedd4 family is located at 8q21, a region frequently amplified in human cancers, including prostate cancer.…”
Section: Bortezomib Prevents Oncogenesis and Bone Metastasis Of Prostmentioning
confidence: 99%
“…SMAD family member 7 (Smad7) negatively regulates the TGF-β/SMAD signaling phosphorylation of R-SMADs (Luo et al, 2014 ). In addition, Smad7 recruits the HECT-type E3 ubiquitin ligases Smurf1, Smurf2, and NEDD4 (Farooqi et al, 2011 ), leading to degradation of the targeted protein TGF-β RI. Ubiquitin-specific protease 4 (USP4) augments TGF-β signaling through the prevention of TGF-β RI degradation (Zhang et al, 2012 ).…”
Section: Transforming Growth Factor-β Signalingmentioning
confidence: 99%